Study of the isomeric yield ratio in the photoneutron reaction of natural holmium induced by laser-accelerated electron beams - Zhang, Jingli; Qi, Wei; Fan, Wenru; Cao, Zongwei; Luo, Kaijun; Tan, Changxiang; Zhang, Xiaohui; Deng, Zhigang; Zhang, Zhimeng; Li, Xinxiang; Yuan, Yun; Luo, Wen; et al. (Frontiers in Astronomy and Space Sciences, 2023)
An accurate knowledge of the isomeric yield ratio (IR) induced by the photonuclear reaction is crucial to study the nuclear structure and reaction mechanisms. Experiments for producing 164m, g Ho by laser-induced photoneutron reactions were performed on the XingGuangIII laser facility at the Laser Fusion Research Center in Mianyang. The γ-ray spectra of activated Ho foils were off-line detected, showing clearly two characteristic γ-ray lines at 73.4 and 91.4 keV. Since the direct transitions from 164m Ho were not successfully observed, we propose to extract the IR of 164m, g Ho using only the photopeak counts from the ground-state decay. The production yields of 164m, g Ho are extracted to be (0.45 ± 0.10) × 10 6 and (1.48 ± 0.14) × 10 6 per laser shot, respectively. The resulting IR is obtained to be 0.30 ± 0.08 at the effective γ-ray energy of 12.65 MeV. The present data, available experimental data, and TALYS calculations are then compared to examine the role of excitation energy. It is found that besides the giant dipole resonance, the excitation energy effect also plays a key role in the determination of IR.